2022
DOI: 10.1111/anae.15672
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric analgesia and anaesthesia in SARS‐CoV‐2‐positive parturients across 10 maternity units in the north‐west of England: a retrospective cohort study

Abstract: Since the start of the COVID-19 pandemic, few studies have reported anaesthetic outcomes in parturients with SARS-CoV-2 infection. We reviewed the labour analgesic and anaesthetic interventions utilised in symptomatic and asymptomatic parturients who had a confirmed positive test for SARS-CoV-2 across 10 hospitals in the north-west of England between 1 April 2020 and 31 May 2021. Primary outcomes analysed included the analgesic/anaesthetic technique utilised for labour and caesarean birth. Secondary outcomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(81 reference statements)
1
8
0
Order By: Relevance
“…A large retrospective cohort study from northwest England encompassing ten hospitals and 57,800 births showed that the labor epidural anesthesia rate was not significantly increased or decreased due to the COVID-19 pandemic. 16 This was a similar finding in our study, which did not find a significant difference in the overall numbers of neuraxial placed. Patkar-Kattimani et al also described no significant difference in the number of labor epidural analgesia techniques performed before and during the pandemic in a tertiary maternity center in the UK.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…A large retrospective cohort study from northwest England encompassing ten hospitals and 57,800 births showed that the labor epidural anesthesia rate was not significantly increased or decreased due to the COVID-19 pandemic. 16 This was a similar finding in our study, which did not find a significant difference in the overall numbers of neuraxial placed. Patkar-Kattimani et al also described no significant difference in the number of labor epidural analgesia techniques performed before and during the pandemic in a tertiary maternity center in the UK.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…Data from the UK Obstetric Surveillance System (UKOSS) reported ICU admission rates during pregnancy varying from 7.9% to 16% during the wildtype, alpha and delta waves of the pandemic, whereas during the omicron wave, the ICU admission rate declined to 3% 8,9 . Our previous work reporting anesthetic outcomes in women who tested positive for SARS‐CoV‐2 in the North West of England, highlighted ICU admission rates of 8% during the antepartum period, increasing to 11% postpartum 4 . Critical care outcomes and maternal morbidity of these women affected by SARS‐CoV‐2 and admitted to ICU in the UK are limited to small case series 10 .…”
Section: Introductionmentioning
confidence: 93%
“…1 Multiple studies in symptomatic pregnant women affected by SARS-CoV-2 across the globe have described significant maternal morbidity, including higher hospitalization rate, cesarean birth, preterm birth, intensive care unit (ICU) admission and the receipt of mechanical ventilation. [2][3][4][5][6][7][8] The ICU admission rate in symptomatic pregnant women with coronavirus disease 2019 in the United Kingdom (UK) has varied throughout the course of the pandemic. Data from the UK Obstetric Surveillance System (UKOSS) reported ICU admission rates during pregnancy varying from 7.9% to 16% during the wildtype, alpha and delta waves of the pandemic, whereas during the omicron wave, the ICU admission rate declined to 3%.…”
Section: Introductionmentioning
confidence: 99%
“…The liberal use of neuraxial labor analgesia may reduce the need for emergency general anesthesia. 61 A systematic review found an association between having a cesarean section and being admitted to the ICU or having COVID-19 pneumonia. The decision to proceed with a cesarean section may be prompted by the need to improve ventilation.…”
Section: Discussionmentioning
confidence: 99%